Quantitative proteomics reveals Polygonum perfoliatum L. ameliorates hepatic steatosis by promoting PPARs/CPT1A/CPT2-mediated fatty acid β-oxidation - Liu, Guanjie; Chang, Ling; Qian, Yihan; Lin, Jiacheng; Shang, Zhi; Xu, Min; Wang, Fang; Sun, Xuehua; Jiang, Yun; Gao, Yueqiu; Kong, Xiaoni (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a predominant contributor to end-stage liver disease in the forthcoming decades. Polygonum perfoliatum L. (PPL) is an herbal medicine with anti-lipid peroxidation and anti-inflammatory properties. However, detailed hepatoprotective effects of PPL against NAFLD and its underlying mechanisms are not fully understood. Here, we found that PPL protects against high fat diet (HFD)-induced hepatic steatosis, lipid peroxidation, and glucose-lipid metabolism dysfunction in NAFLD mice. We therefore performed a label-free quantitative proteomic profiling analysis to determine the effect of PPL treatment on liver tissue proteomics and identified that activated PPARs/CPT1A/CPT2-mediated hepatic fatty acid β-oxidation (FAO) process was significantly altered. In vitro treatment of hepatocytes with PPL confirmed this altered process and FAO inhibitor etomoxir (ETO) attenuated the lipid-lowering activity of PPL in hepatocytes. Ultra-high-performance liquid chromatography/Q Exactive-HFX (UPLC/QE-HFX) was used to determine the material basis of anti-NAFLD activity of PPL. Our results have demonstrated the efficacy and potential mechanisms of PPL as an effective pharmacological therapy of NAFLD.